IDENTIFIKASI PENGUATAN NILAI-NILAI PENDIDIKAN KARAKTER MELALUI BERPIKIR KRITIS GURU BIOLOGI PADA SISWA KELAS XI MAN AMBON - Hanisu Alkarim; Johanis F Rehena; Hasan Tuaputty; Dominggus Rumahlatu (Program Studi Pendidikan Biologi FKIP Unpatti, 2020)
Background: The teacher holds an important role in developing and strengthening the education of students' character in a Biology learning process. The character of the teacher is one of the factors that must be developed in the curriculum. Critical thinking includes character and skills which are two things that can not be separated in a person. Method: This research was conducted in July-August 2018, using a questionnaire distribution method of 60 students and interviews with the head of MAN, deputy head of curriculum, Biology teacher, religion teacher, BK teacher and Committee teacher. Results: This study shows the character of Biology teachers towards class XI students including the Good category, strengthening the character education of students in the bad category, and critical thinking of Biology teachers in the good category, and the relationship of the character of the Biology teacher. Conclusion: Strengthening the value of student character education has a strong relationship that is with a value of 0.867.